Case 3796: Proposal to remove Xenophrys monticola Günther, 1864 (Amphibia: Megophyridae) from the Official Index of Rejected and Invalid Specific Names in Zoology. - Mahony, Stephen (Bulletin of Zoological Nomenclature)
Noticed in BZN 76 (30 April 2019): 2.